Non-coding RNAs and Cardiac Arrhythmias - Šustr, Filip; Stárek, Zdeněk; Souček, Miroslav; Novák, Jan (Advances in experimental medicine and biology, 2020)
Cardiac arrhythmias represent wide and heterogenic group of disturbances in the cardiac rhythm. Pathophysiology of individual arrhythmias is highly complex and dysfunction in ion channels/currents involved in generation or spreading of action potential is usually documented. Non-coding RNAs (ncRNAs) represent highly variable group of molecules regulating the heart expression program, including regulation of the expression of individual ion channels and intercellular connection proteins, e.g. connexins.Within this chapter, we will describe basic electrophysiological properties of the myocardium. We will focus on action potential generation and spreading in pacemaker and non-pacemaker cells, including description of individual ion channels (natrium, potassium and calcium) and their ncRNA-mediated regulation. Most of the studies have so far focused on microRNAs, thus, their regulatory function will be described into greater detail. Clinical consequences of altered ncRNA regulatory function will also be described together with potential future directions of the research in the field.
Keywords: srdce; nekódující RNA; mikro RNA; Ion Channels; MicroRNAs; RNA, Untranslated; lidé; iontové kanály; Heart; srdeční arytmie; Humans; Arrhythmias, Cardiac